2008
DOI: 10.1080/09613210802076328
|View full text |Cite
|
Sign up to set email alerts
|

Re-contextualizing the notion of comfort

Abstract: To what extent can the urgency of climate change and an evolving concept of agency (at the individual and social levels of building users) create a new context for rethinking the notion of comfort? A new, emerging notion of comfort is explored that embraces engagement with new conditions, new experiences, and new types of interactions between inhabitants and building systems and unfamiliar technologies. The emphasis is on communication and dialogue as two dynamic and adaptive processes necessary to achieve opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 24 publications
1
145
0
5
Order By: Relevance
“…Recent sociotechnical research in the built environment and retrofit has begun to draw attention to this issue (e.g. Cole et al, 2008;Foulds et al, 2013;Gram-Hanssen, 2010;Haines & Mitchell, 2014;Ingle, Moezzi, Lutzenhiser, & Diamond, 2014;Judson & Maller, 2014;Karvonen, 2013;Tweed, 2013;Shove et al, 2008;Vlasova & Gram-Hanssen, 2014). This movement and the limitations of current POE have precipitated the authors' explicit adoption of the socio-technical approach for the FLASH project.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent sociotechnical research in the built environment and retrofit has begun to draw attention to this issue (e.g. Cole et al, 2008;Foulds et al, 2013;Gram-Hanssen, 2010;Haines & Mitchell, 2014;Ingle, Moezzi, Lutzenhiser, & Diamond, 2014;Judson & Maller, 2014;Karvonen, 2013;Tweed, 2013;Shove et al, 2008;Vlasova & Gram-Hanssen, 2014). This movement and the limitations of current POE have precipitated the authors' explicit adoption of the socio-technical approach for the FLASH project.…”
Section: Discussionmentioning
confidence: 99%
“…In recontextualizing comfort, Cole et al (2008) came close to this mutuality by highlighting the possibility of interactive adaptation between occupants and new technology. Informed by social theorists' work on human agency (Bourdieu, 1977;Giddens, 1984;Habermas, 1989) they suggested that engagement, dialogue and communication at all stages are required to enable occupants to play an active role in operating increasingly complex systems associated with buildings.…”
Section: Interactive Adaptationmentioning
confidence: 99%
See 3 more Smart Citations